Gastronomi Urban: Transformasi Kuliner Viral Menjadi Objek Wisata Di Kawasan Ciwidey - Nindita Fajria Utami; Risris Hari Nugraha; Shandra Rama Panji Wulung (Sosietas: Jurnal Pendidikan Sosiologi, 2024)
The phenomenon of viral culinary delights has become a significant driver of urban tourism, including in Bandung. This article aims to analyze the transformation of viral culinary offerings into major tourist attractions, focusing on Ciwidey, one of Bandung's popular culinary destinations. Using a qualitative approach and case study method, this research integrates in-depth interviews, field observations, and social media analysis. The findings reveal that viral culinary trends, such as salted skewers in Ciwidey, not only enhance tourism appeal but also create complex social, economic, and cultural impacts. On one hand, the popularity of these culinary delights stimulates the growth of small businesses (UMKM) and increases the local community's income. On the other hand, it presents challenges such as overcrowding, shifts in social interactions, and risks to environmental sustainability. This article underscores the importance of collaboration between governments, business owners, and local communities to manage the phenomenon of viral culinary trends in a sustainable manner